Ophthalmological manifestations in antiphospholid syndrome – case series - Ostrowska-Spaleniak, Aleksandra; Krix-Jachym, Karolina; Rękas, Marek (Klinika Oczna / Acta Ophthalmologica Polonica, 2019)
The antiphospholipid syndrome is a systemic autoimmune hypercoagulable state, with highly variable symptomatology such as venous and /or arterial thrombosis and obstetric morbidity. Its serological markers are antiphospholipid antibodies: lupus anticoagulant, anticardiolipin antibodies and anti-β2-glycoprotein I antibodies. Deep vein thrombosis is the most common complication of antiphospholipid syndrome occurring in about half of patients; thrombotic events may affect many important organs: lungs, skin, brain, liver, kidneys, adrenal glands, heart and eyes. Ocular involvement may occur in about 80% of patients with antiphospholipid syndrome and may be its first clinical manifestation. Retinal arterial and vein occlusion accompanied by various neurological symptoms, such as anterior ischemic optic neuropathy and amaurosis fugax, can be considered as typical of antiphospholipid syndrome. The complications of antiphospholipid syndrome are treated with anticoagulants in order to prevent further thrombotic events.